The effect of powdered pectin on the flavor and texture of canned mango scoops - San Agustin, Marita U.; Guzman, Matilde P. (1964.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Pectin; Mango scoops, Canned